Risk sharing and layoff risk in profit sharing - Fabella, Raul V. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1995)
We show that if the employer is risk averse, however slightly, there is always a profit sharing contract that will Pareto-dominate the spot wage contract in the sense of pure risk sharing. The smaller is employer risk aversion, the narrower is the room for profit sharing. The higher the workers value employment stability (less layoff risk), the more Pareto attractive is profit sharing regardless of employer risk aversion.